The Dominican Order in Late Medieval and Early Modern History. Issue 11 (November 2013) - Vose, Robin
Abstract: Firmly established by the 14th century throughout much of Europe, men and women associated with the Dominican Order emerged as leading voices within the Roman Catholic Church during its difficult yet also creative and expansive transition from late medieval to early modern times. Dominican friars, nuns, and growing numbers of lay penitents who accepted their supervision all contributed to the emergence of new spiritual directions and cultural productions, while also in many instances firmly upholding conservative and strictly disciplined versions of Catholic orthodoxy. This essay briefly surveys recent approaches to the Dominican legacy as it unfolded from the crisis years of Black Death and Schism, through the challenges of Observant, Protestant, and Tridentine reform movements, to the dawning of a global colonial age.